The influence of suicide examples in the media on teenagers and young people - Gailienė, Danutė; Trofimova, Jelena; Žemaitienė, Nida; Miliukaitė, Agnė (Psichologija, 1999)
The goal of this study was to determine the influence of suicide examples in media on teenagers and young peoples’ emotions and thoughts about suicide imitation. Conclusions: 1) Teenagers and young people encounter with examples of suicidal behavior in all forms of media, mostly, newspapers and television. 2) Some of young people experience a high emotional effect of suicide description or depiction. 3) Models of suicidal behavior presented in media mostly affect the young people who are experiencing existential frustration and have more expressed suicidal tendencies.